The Influence Of Regional Capital Inclusion On The Financial Performance Of Bumd Dki Jakarta: The Impact Capital Participation Of Local Governance To Financial Performance Of Local Owned Enterprises Dki Jakarta - Ahmad Awaluddin Aras (Universitas Islam Lamongan, 2023)
This research was conducted with the aim of finding One way to develop regional financial independence is through the establishment of Regional Owned Enterprises (BUMD). The realization of BUMD's achievements in maximizing regional capital participation is still relatively weak. This research discusses the influence of regional capital participation on the financial performance of BUMD DKI Jakarta. This research uses quantitative methods with panel data regression analysis techniques in the form of random effect models. The control variables used are age, total assets, share ownership, return on equity and return on assets. The research results show that regional capital participation, return on assets, age and total assets have a positive and significant effect on financial performance. At the sub-level BUMD that received regional capital participation, it was found that return on equity had a positive and significant effect on financial performance..